THEORETICAL BASIS OF FORMATION OF EFFECTIVE POPULATION EMPLOYMENT - Козьмук, Наталія; Решетник, Мар’яна (Socio-economic relations in the digital society, 2019)
The increasing influence of external factors, new trends in development, the limitation of traditional sources of growth of gross domestic product have objectively determined the urgent need to find opportunities for effective employment in the legal sector of the economy, to overcome existing disparities and contradictions in the development of national and local labor markets, reducing. Employment is an important indicator of social progress in society. Employment of the population can be considered as a set of economic, legal, social and otherrelations connected with providing working population with jobs. Employment can be seen as a process of securing jobs. Employment of the population can be regarded as a relative category, that is, the degree of participation of the working population in income-generating social work. With the development of a market economy and the worsening employment problems in the world economy, in the context of scientific and technological progress, atypical forms of employment are displacing standard employment. The level of employment is influenced by macroeconomic factors: socio-economic system, state policy. Employment is influenced by microeconomic factors that depend on a particular method, the purpose of the form of organization of production, the level of development of productive forces. Labor remuneration is one of the important prerequisites for effective human employment. Employment, which ensures the efficient use of available labor resources and their fullest involvement in the process of social production, while ensuring the maximum satisfaction of personal and public needs of the population, can be recognized as effective. Effective employment involves ensuring the right income, health, enhancement of personality, growth of educational and professional levels for each member of society based on the growth of social productive work.
Keywords: employment; effective employment; forms of employment; structure of employment; labor resources